Synergistic behavioral and neuroplastic effects of psilocybin-NMDAR modulator administration - Tom Ben-Tal; Ilana Pogodin; Alexander Botvinnik; Tzuri Lifschytz; Uriel Heresco-Levy; Bernard Lerer (Translational Psychiatry)
Abstract The full therapeutic potential of serotonergic psychedelics (SP) in treating neuropsychiatric disorders, such as depression and schizophrenia, is limited by possible adverse effects, including perceptual disturbances and psychosis, which require administration in controlled clinical environments. This study investigates the synergistic benefits of combining psilocybin (PSIL) with N-methyl-D-aspartate receptor (NMDAR) modulators D-serine (DSER) and D-cycloserine (DCS) to enhance both efficacy and safety. Using ICR male mice, we examined head twitch response (HTR), MK-801-induced hyperlocomotion, and neuroplasticity related synaptic protein levels in the frontal cortex, hippocampus, amygdala, and striatum. Our results indicate that PSIL significantly increased HTR—a surrogate measure for hallucinogenic effects—which was reduced by the co-administration of DSER or DCS in a dose-dependent manner. Similarly, combining PSIL with DSER or DCS significantly decreased MK-801-induced hyperactivity, modeling antipsychotic effects. Neuroplasticity-related synaptic protein assays demonstrated that the PSIL-DSER combination enhanced GAP43 expression over all 4 brain examined and overall expression of the 4 assayed synaptic proteins in the hippocampus, while PSIL-DCS elevated PSD95 levels across all 4 brain regions, suggesting a synaptogenic synergy. These findings support the hypothesis that combinations of SP with NMDAR modulators could optimize the therapeutic potential of SP by mitigating adverse effects and enhancing neuroplasticity. Future studies should focus on refining administration protocols and evaluating translational applicability for broader clinical use.